Hedging volatility: different perspectives compared - Ogg, Richard (Financial Accounting, 2021)
The accuracy of the Black and Scholes (1973) delta and vega neutral portfolio for a vanilla option was compared to a benchmark set by the Heston (1993) model in a stochastic volatility environment. The Black-Scholes portfolio was implemented using a fixed volatility and by implying volatility from the market. Additionally, a portfolio based on the Dupire (1994) local volatility model was also compared. It was found that a portfolio consisting of two short maturity options with matching maturities was best hedged by the Black-Scholes model when using implied volatility. This result was not maintained when the two options had mismatching maturities as the proportional differences in the vegas no longer cancelled. Further examination was completed on the type of financial instruments used to hedge volatility, comparing portfolios that consisted of an additional option and a variance swap to offset any vega. It was found that both hedged the option well, with similar accuracies.